Da mina ao litoral: uma análise da atuação do Sindicato dos Trabalhadores em Empresas Ferroviárias dos Estados do Maranhão, Pará e Tocantins STEFEM - OLIVEIRA, Mayara Sousa de (2024)
This dissertation deals with the analysis of the representative institution of railway-port workers called the Union of Workers in Railway Companies of the States of Maranhão, Pará and Tocantins - STEFEM. The union's trajectory, marked by major changes, especially in the context of the companies represented, such as the privatization of Vale, makes us reflect on how class unionism is an important exponent in organizing workers and defending social and economic rights. The analysis of the research object focuses on examining the union in its complexity. Issues such as union action, mobilization strategies, collective action repertoires, relations with workers, activities carried out by the board of directors, among other topics, are the main focus of the analysis with regard to the union studied. The companies represented are also the target of the proposed investigation. The company Vale S.A., which has the largest contingent of workers represented by the union and a strong history of union struggles interspersed in its historical context because it is a former state-owned company, has been analyzed in greater depth. In order to support this work, the main perspectives used to construct the dissertation are articulated with sociological theories in the field of Labor and Collective Actions, which guided the exploratory and quantitative research. This work is based on an expanded reading of bibliographical studies appropriate to the research, documentary research of internal regimes and collective agreements, direct observation of the union space studied and semi-structured interviews. In short, a study was carried out on Brazilian trade unionism and its influence on the regional scope through the class trade unionism of railroad dockworkers in the states of Maranhão, Pará and Tocantins. Based on this investigation, we found elements that condition the organization and defense of the collective interests of the working class, such as better working conditions, fair wages and benefits, and their contributions to the social world of work through workers' solidarity and struggle.